Estimating life-expectancy changes for medical decision making: New approximations - Gu, Chushu (University of Ottawa (Canada), 2006)
Life-expectancy and Life-years lost are frequently used and analyzed indices of survival. Life tables and Markov models are two exact approaches to calculate these indices; however cumbersome calculation limits their usage in real situations. Some simple approximation approaches have therefore been developed since a convenient and accurate approximation is critical both to develop a treatment plan of a patient by physicians and to assess health policies by health policy makers. These approximation approaches include the DEALE (Declining Exponential Approximation of Life Expectancy), new DEALEs, the IPH method (A method developed at Institute of Population Health, University of Ottawa) and the Keyfitz approach. A new approach has been developed to achieve better accuracy and maintain ease of application by extending the Keyfitz approach. To make the new approach less dependent on age-stratified tabulations, a convenient formula for the EME (Established market economics) region is developed. Its accuracy, robustness, and ease of application are demonstrated.
Keywords: Health Sciences, Health Care Management.; Engineering, System Science.